Thai Secondary School of Representation about ICT Understanding in Proposed Learning Model - Kinboon, N.; Suwannoi, P.; Koul, Rekha (ELSEVIER SCIENCE BV, 2014)
This research aimed to explore the teachers’ and students’ understanding of science concepts in secondary schools in Thailand and to suggest to proposed ICT learning model to make students aware of current science issues impacting on the society. A total of 165 (15 teachers and 150 Students) participated in the study. Students were from years 10, 11and 12 who studied information and communication technology subject in year 2012 and teachers who taught the same course. Research instruments consisted of a questionnaire, interview form for teachers, classroom observations and video recordings. The study was based on a widespread popular and influential conceptual modeling representation theory. In the model, ICT supports internal learning processes of representation (creating and self-organizing knowledge) and promotes collaboration and interaction (social processes and making meaning). Based on the results of this study a model has been developed in association with researchers from Western Australia and Thailand. It will be implemented in Thailand in early 2013. This model is tended to be more connected to people outside of the classroom rather than isolated, and the learning process tended more often to contribute to productive outcomes such as the solving of authentic problems.